Pelembagaan Partisipasi Masyarakat sebagai Upaya Implementasi Sistem Informasi Desa - Fadjarini Sulistyowati; MC Candra Rusmala Dibyorini; B Harisaptaning Tyas (Jurnal Aspikom)
This research aims to find synchronization of district government policy, the use of Sistem Informasi Desa, and participation of people in Terong Village, in Dlingo Sub District of Bantul. This research applied a group model based on collective identity with some modifications as an appropriate institutionalization model of community participation suited with local wisdom in Terong village. This research uses qualitative descriptive method. Data derived from observation, focus group discussions and interviews. Data analysis has been done through interactive techniques. The result of this research is a model of a group-based institutionalization of community participation for utilization Village Information System supported by Combine Resource Institution (CRI) and the goverment of Bantul.